FORMAÇÃO DE ARTE/ EDUCADORES: um estudo sobre a formação pedagógica do curso de licenciatura em Artes Visuais da Universidade Federal do Maranhão - MELO, Suzana Alves dos Santos (2019)
ABSTRACT This research deals with the pedagogical development of the Degree course in Visual Arts of the Federal University of Maranhão, considering in its historical trajectory the curricular reformulations occurred from 2010. For the purpose, we set as general objective to analyze the process of curricular reconfiguration of the Degree course in Visual Arts of UFMA in the last ten years, identifying its propelling forces and their possible effects on the pedagogical formation of the Art teacher. And as specific objectives: analyze the historical trajectory of the degree course in Visual Arts of UFMA and the characteristics of its curricular reformulations in the last ten years; identify the propelling forces underlying to the curricular reformulations that occurred in the last ten years; analyze the articulation between the specific matrix of the visual arts and the pedagogical matrix in the PPC of the course; identify the possible effects of the curricular changes of pedagogical formation of the future teacher in Art. The construction of the research object was based on the qualitative approach in a critical perspective, in which we used as documentary research instruments, for the verification of the official documents related to the legislation of the teacher training the Pedagogical Projects of the course; and the semistructured interview with students and teachers of the referred course, one of the teachers of the Department of Education I and students who graduated of degree in Arts Education of UFMA. For the analysis and processing of data, we used the Discursive Textual, systematized from the studies of Moraes and Galiazzi(2016). The theoretical contribution of the research considers the studies of André (2010; 1999); Tardif(2014); Imbernón (2010); Ramalho, Nunes and Gauthier (2003); Tanuri (2000); Pimenta(2005); Duarte (2003;2010); Martins and Duarte (2010); Freitas (2002;2010); arbosa(1998;2012), Tourinho (2012); Reis(2003); Santana(2013),among others. From the data analysis, we identified that the reformulations were driven by the need to adapt the course to the curricular guidelines, as well as, intended to define the identify of the course, which seeks to simultaneously add the formation of the artist and the art teacher. In the most recent curricular reformulation, there was an effort to promote the articulation between the theoretical-pratical axis of the visual arts and the axis of the pedagogical formation, however this articulation still has not been consolidated consistently, remaining with a challenge to the teacher training.